Attitudes, perceptions and knowledge among men who have sex with men towards the blood donation deferral policy in Israel. - Itzchak Levy; Liraz Olmer; Yuval Livnat; Adir Yanko; Eilat Shinar (PLoS ONE)
Background Men who have sex with men (MSM) are permanently deferred from donating blood in Israel. Pressure to change this policy exists, despite data showing higher prevalence and incidence of HIV in MSM. A survey was conducted to evaluate current knowledge, attitudes, perceptions and compliance if deferral was changed. Study design and methods Anonymous survey was published in a gay-oriented website, collecting demographic information, history of blood donation, attitudes, knowledge and compliance with permanent versus temporary deferral. Responses were analyzed given 1 point for every "yes" response (0-7 points). Student's t-test was applied to compare differences between continuous variables. Correlations were described with the Pearson correlation coefficient. Results Responses from 492 MSM were analyzed. Average age was 31±9 years. 76% donated blood at least once, mostly for social solidarity (score of 3.2 on 1-5 scale). Tests seeking or protest scores were 1.7 and 1.6, respectively. 66% were unaware of the higher risk of HIV transmission by MSM, or the potential to infect 3 recipients. Knowledge regarding HIV transmission by blood positively correlated with knowledge regarding other routes of HIV transmission (r = 0.11; p = 0.03), age (r = 0.10; p = 0.04), and higher rate of non-compliance with the current deferral policy (OR = 1.9; p = 0.02). Activism for LGBT rights was associated with lower risk for non-adherence (OR = 0.5; p = 0.03). If temporary deferral is introduced 66% will comply with the new policy, but 23% will continue to donate as long as MSM deferral policy is in place. Conclusion A high proportion of MSM do not comply with the current lifetime deferral. This may partially change if temporary deferral is introduced.